Lola's war: rape without punishment - Simić, Olivera (Palgrave Macmillan, 2023)
This longitudinal study is based on the story of Lola, who was gang raped during the war in Bosnia and Herzegovina in 1992. At the time, she was in a detention camp with her young children. Only one of Lola's several perpetrators was convicted but his sentence of six years of imprisonment has never been actioned by the Bosnian judiciary. Lola's rapist is still free and she lives in continual fear that he will retaliate against her and her children for her role in his trial